Supply chain leakage of greenhouse gas emissions and supplier innovation. Issue 3 (27th November 2022) - Song, Sining; Dong, Yan; Kull, Thomas; Carter, Craig; Xu, Kefeng
Abstract: Climate change is a major global risk and a key driver for greenhouse gas emissions reduction. Yet, firms' internal emissions reduction may create a leakage leading to higher emissions in the supply chain. The related literature suggests that the pollution‐haven hypothesis explains such emissions leakage. In contrast, we explore an alternative reason for supply chain leakage, which is related to optimization of supply chain activities and supply chain innovation. Based on panel data from Bloomberg Environmental, Social, and Governance and Bloomberg Supply Chain, we estimate our models at a dyadic (i.e., firm and supplier) level using two‐way cluster‐robust standard error, treating various sources of endogeneity. We find empirical evidence of a supply chain leakage effect—a higher level of a supplier's emissions is associated with a lower level of a firm's internal emissions. More importantly, the supplier's innovation can be a major reason behind the leakage; the supply chain leakage effect is stronger when a supplier is more innovative. Furthermore, the role of innovation is strengthened when a supplier invests in eco‐innovation and has technological capabilities similar to those of the focal firm. Our findings suggest that supply chain leakage may not be completely driven by the pollution‐haven effect, but instead is associated with supply chain optimization and innovation that may be beneficial in the long run.